Pemberian Terapi Edukasi terhadap Kecemasan Pada Keluarga Dengan Anggota Keluarga Menderita STEMI di Ruang ICU RSUD dr. T.C. Hillers Maumere - Maria Mei Londa; Ode Irman (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
ST Elevation Myocardial Infarction (STEMI) is an emergency condition caused by rupture of atheroma plaque in the coronary arteries which blocks blood flow to the heart. If this condition is not treated immediately it can result in disability and death. The family has an important role in determining the treatment needed by the patient in the Intensive Care Unit. However, families are vulnerable to experiencing anxiety which will slow down the process of decision making and patient care, so the role of nurses is very important in overcoming family anxiety. One of them is the intervention of providing educational therapy. The aim of this research is to provide nursing care to Paisen families with STEMI to overcome anxiety. The type and research design used is a descriptive method with a case study approach. The subjects of this case study are families who have met the inclusion criteria, namely the patient's wife with anxiety problems, can read and write, and is willing to be a respondent. The participant collection technique used purposive sampling. The research instrument used the HARS (Hamilton Anxiety Raiting Scale) questionnaire. The research was carried out in 2 days. The research results show that educational therapy intervention can reduce the patient's family's anxiety from severe to mild anxiety. For this reason, nurses are expected to be able to provide social support both informationally and emotionally so that there is no anxiety in the family.